Application Exploration and Prospect Analysis of Electrical Engineering Automation in the Field of Smart Grids - Ma, Ruiqi (International Journal of Mechanical and Electrical Engineering, 2025)
This paper expounds the definition, characteristics, advantages and current development status of smart grids, analyzes the basic concepts, technical systems, application scopes of electrical engineering automation as well as its application and actual effects in traditional power grids, conducts an in-depth study on the specific application of electrical engineering automation in smart grids, and looks forward to its development prospects in the field of smart grids, In addition, this article also conducts in-depth discussions on how electrical engineering automation can be deeply integrated with traditional power grids, contributing to the ultimate promotion of the efficient development of the energy system and the prosperity of the social economy.